2020
DOI: 10.1016/j.tre.2020.102060
|View full text |Cite
|
Sign up to set email alerts
|

A healthcare logistic network considering stochastic emission of contamination: Bi-objective model and solution algorithm

Abstract: Highlights A novel healthcare waste location-routing problem is developed with a new perspective in healthcare logistics networks. A stochastic essence for the emission of contamination is considered. The management of medical wastes in Coronavirus Disease 2019 is focused. A real case study is modeled to manage the logistics of infectious and non-infectious healthcare wastes. A Multi-Objective Water-Flow like Algorithm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(15 citation statements)
references
References 55 publications
(82 reference statements)
0
12
0
Order By: Relevance
“…During the COVID-19 pandemic, several articles have been published considering its consequences on supply chains (e.g. Govindan et al, 2020;Nikzamir & Baradaran, 2020). However, we found no research that designs a viable healthcare supply chain network that effectively works in both pandemic and normal statuses.…”
Section: Contributions Of This Studymentioning
confidence: 69%
“…During the COVID-19 pandemic, several articles have been published considering its consequences on supply chains (e.g. Govindan et al, 2020;Nikzamir & Baradaran, 2020). However, we found no research that designs a viable healthcare supply chain network that effectively works in both pandemic and normal statuses.…”
Section: Contributions Of This Studymentioning
confidence: 69%
“…The model was validated by using a case study from Iran and demonstrated a trade-off between objectives for better managing waste flows. Nikzamir and Baradaran (2020) presented a bi-objective model considering costs and emissions of contamination that could be intensified during the COVID-19 outbreak. They modeled the transferring time between nodes as random variables and used a meta -heuristic algorithm for solving that complex model.…”
Section: Literature Reviewmentioning
confidence: 99%
“…They contribute to the literature by incorporating into the model the fuel consumption and carbon dioxide emissions along the collection routes. Nikzamir and Baradaran [ 38 ] develop a mixed-integer nonlinear programming (MINLP) formulation for healthcare waste location and routing problem. The model includes stochastic transfer times between healthcare and treatment centers and emission of contamination.…”
Section: Literature Surveymentioning
confidence: 99%